2020
DOI: 10.1111/2047-3095.12274
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Diagnosis Risk for Delayed Surgical Recovery (00246) in Adult and Elderly: A Case‐Control Study

Abstract: The study's objective was the clinical validation of the nursing diagnosis Risk for delayed surgical recovery (00246). METHOD: Case control study was conducted in a university hospital; the charts of 239 patient, 71 cases and 168 controls. Odds ratio was calculated for the association between each risk factor and the outcome of delayed surgical recovery. RESULTS: Risk factors with higher odds of association were malnutrition, pain, and postoperative emotional response. The associated conditions were perioperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, the three most frequently identified NDs in our sample were risk NDs, demonstrating the valuable role of nurses in surgical risk assessment and prevention for establishing a standard of safety and quality of care. This was confirmed in the study by Rembold et al (2020) , who showed how identification of the risk factors of clinical practice enables implementation of interventions to prevent or reduce complications during surgical recovery. Eleven NDs were identified as HF-NDs in our sample.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, the three most frequently identified NDs in our sample were risk NDs, demonstrating the valuable role of nurses in surgical risk assessment and prevention for establishing a standard of safety and quality of care. This was confirmed in the study by Rembold et al (2020) , who showed how identification of the risk factors of clinical practice enables implementation of interventions to prevent or reduce complications during surgical recovery. Eleven NDs were identified as HF-NDs in our sample.…”
Section: Discussionmentioning
confidence: 75%
“…With respect to the clinical indicator evidence of the interruption of the healing of the surgical area (sensitivity: 0.88; specificity: 0.99), in the studies conducted by Santana et al (2018) and Rembold, Santana, Lopes, and Melo (2020) this indicator also presented a high prognostic value for delayed surgical recovery.…”
Section: Discussionmentioning
confidence: 98%
“…Of the variables assessed and identified in our review, BMI, 14,55 ASA, 8,56 physical function, 12,57,58 psychological-emotional wellbeing, 9,[59][60][61] comorbidities, 9 previous surgery, 62 and pain 10,13,16,56 are known risk factors for surgical complications and unidimensional recovery. In our review, not all identified risk factors showed an effect on multidimensional recovery in every study.…”
Section: Effect Of Risk Factors Varied By Direction and Surgical Popu...mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Traditional postoperative outcomes have been well investigated in this population: absence of complications, adverse symptomatology (i.e., nausea, vomiting, pain, hypothermia, respiratory distress), length of hospital stay, quality of life, and resource utilization. 1,11,[14][15][16][17] While these traditional performance indicators influence a patient's postoperative status, they are unidimensional and thus may not adequately define the patient's quality of recovery. This has led to redefining postoperative recovery as a multidimensional trajectory occurring in many of the functional domains mentioned above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation